Shot noise and charge at the 2/3 composite fractional quantum Hall state - Bid, Aveek; Ofek, N; Heiblum, M; Umansky, V; Mahalu, D (Physical review letters, 2009)
The exact structure of edge modes in "hole conjugate" fractional quantum Hall states remains an unsolved issue despite significant experimental and theoretical efforts devoted to their understanding. Recently, there has been a surge of interest in such studies led by the search for neutral modes, which in some cases may lead to exotic statistical properties of the excitations. In this Letter, we report on detailed measurements of shot noise, produced by partitioning of the more familiar 2/3 state. We find a fractional charge of (2/3)e at the lowest temperature, decreasing to e/3 at an elevated temperature. Surprisingly, strong shot noise had been measured on a clear 1/3 plateau upon partitioning the 2/3 state. This behavior suggests an uncommon picture of the composite edge channels quite different from the accepted one.